Gender Communication of Batik Air Flight Attendants in Improving Customer Service - Bahruddin, Muh.; P, Rega Ayu (representamen, 2024)
Gender perception in Indonesia is influenced by sociological and cultural processes that focus on the relationship between gender and work in society. Meanwhile, people often associate gender with a certain gender. In economic challenges, such as gender inequalities in education, physical quality, labor, and migration, exacerbate gender imbalances. Cultural norms and values contribute to a more diverse workforce. Based on these problems, this study aims to provide an overview of how the gender communication strategy carried out by flight attendants in improving service during their time as employees at Batik Air airline. The method used in this study uses a descriptive qualitative approach. Primary data was obtained from a semi-structured interview process with three informants who work as Batik Air flight attendants with the criteria of having at least 5 years of experience in Batik airlines. Meanwhile, secondary data is obtained through the process of collecting literature data such as articles and other sources, both from books and national and international journals. The interview focused on service during being a Batik Air flight attendant, as well as the experience of dealing with customers, especially those who are in contact with gender. The viewpoint used in analyzing the data is gender communication. The results of the research findings revealed that: 1). Flight attendants are the brand image of the airline, representing the company's commitment to safety and professional service, 2) flight attendants serve as a representation of the airline's professional service and image, ensuring effective communication and understanding of passenger situations and conditions. In achieving success in terms of professional services, communication strategies are seen from the analysis of the situation, who the target is, what message is to be conveyed, the media used, and the results obtained. Keywords: Batik Air, Communication, Airlines, Flight Attendants, Strategy